PENGARUH CUSTOMER EXPERIENCE, EASY OF USE DAN CUSTOMER TRUST TERHADAP REPURCHASE INTENTION SITUS JUAL BELI ONLINE SHOPEE DIKALANGAN MAHASISWA KOTA SURAKARTA - Verina, Tya; Susanti, Ari (Department of Islamic Education Management, 2022)
The Effect of Customer Experience, Easy of Use and Customer Trust on Repurchase Intention Online Shopee Buying Sites Among Students in the City of Surakarta The development of the Marketplace in Indonesia experienced a very significant increase in growth. Online site services or electronic money services are increasing. The occurrence of repurchase intentions or online purchasing activities repeatedly makes customers feel easy, comfortable, and trusting. Someone will trust online shopping sites and return and market products with others, namely Customer Experience, Ease of Use, and Customer Trust. The purpose of this study was to determine the effect of Customer Experience (X1), Easy of Use (X2) and Customer Trust (X3) on Repurchase Intention (Y) Shopee online buying and selling site among Surakarta City Students. The instrument testing technique is validity and reliability test, classical assumption test using normality, multicollinearity, and heteroscedasticity. The testing of this research uses hypothesis testing, linear regression analysis, t test, and the coefficient of determination and data processing in this study uses the SPSS21 system. Data collection using purposive sampling technique by taking 100 sample questionnaires. The final result of this study shows that Customer Experience (X1), Easy of Use (X2) and Customer Trust (X3) have a significant effect on Repurchase Intention (Y).